Durability Design Approach and Exposure Conditions in Eurocode, British Standard and ISO 13823 Standards: A Review - Al-Haddad, Diala Basim (2024)
This open access book presents contributions on a wide range of scientific areas originating from the BUiD Doctoral Research Conference (BDRC 2023)